Outcome of Scalp Visor Flap for Post-Burn Facial Alopecia Reconstruction in Male Patients (Medical Forum Monthly, 2024)
Objective: To study the versatility and aesthetic outcomes of scalp visor flap for post burn scar alopecia reconstruction in male patients.Study Design: Case series studyPlace and Duration of Study: This study was conducted at the Department of Plastic Surgery, Jinnah Hospital, Lahore from May 2014 to June 2017.Materials and Methods: A total of seven male patients were included. According to the size of defect created scalp visor flap was raised at galea-periostium space preserving superficial temporal artery bilaterally. Flap is rotated on recipient area as bucket handle for moustache and beard reconstruction and donor site is skin grafted or closed primarily. Division and in setting carried out after 3 weeks and excess flap returned to cover the temporal region.Results: There were 3 post flame burn, 2 chemical burn and 2 electric burn patients. Two patients required upper lip and 5 required both upper and lower reconstruction with donor site either skin grafted or closed primarily. All 7 flaps survived completely. Out of 7 patients, 4 (57.1%) have excellent, 2 (28.6%) have good and 1(14.3%) has fair results.Conclusion: The scalp visor flap is a reliable and versatile hair bearing flap for male post burn scar facial alopecia management with excellent aesthetic outcome.